Atratividade e palatabilidade de diferentes proteínas hidrolisadas para a espécie ornamental Betta splendens (Regan, 1910) - Oliveira, Suzana Raquel de (2020)
The objective of this study was to define attractivity and palatability of juvenile Betta splendens when fed diets containing hydrolyzed proteins derived from poultry and swine. The study design was composed of five experimental diets containing tilapia meal (FPT) and a 5% inclusion of different protein sources: hydrolyzed poultry meal (PHF), hydrolyzed porcine liver meal (PHS), hydrolyzed feather meal (PHP), and hydrolyzed porcine mucosa meal (PHM). Five juveniles were utilized with an average weight of 2.92 ± 0.24 g, and an average length of 3.24 ± 0.39 cm. Feeding management was determined via random drawings of both specimens and feed type, with a feeding schedule of four times per day, in which feeding habits were observed regarding time of capture of the first pellet, number of pellet rejections, number of approaches without pellet capture, and number of pellets consumed. The data was submitted to ANOVA, and subsequently Duncan’s MRT was performed with a 5% significance. The greatest index of attractivity and palatability was encountered with PHS at 12.46%, followed by PHM at 11.62%, PHP at 11.02%, and FPT with the lowest result at 10.33%. The significant effect (P < 0.05) was observed in the feeding behavior regarding the consumption of pellets, in which PHS represented an increase of 27.5% in final consumption, PHF with an increase of 20.68%, PHM with an increase of 12.06%, and PHP with an increase of 6.89%, when compared to FPT alone. PHS, which was proven to be the most attractive and palatable, increased the overall feed consumption in comparison to FPT. Thus, PHS may be utilized to effectively increase consumption in Betta splendens juveniles as a substitute to tilapia meal, and as a means of reducing feed waste in aquariums of this species.